Prática educativa da Escola Agropecuária Federal de Sertão : uma experiência de mediação entre formação cidadã e formação profissional - Chaves, Nizete Zanolla (2008)
This work analyzes the project of the technical course in Agricultural with emphasis in Fruit Culture, developed by the Federal Agro Technical School of Sertão, offered in the city of Vacaria, intending to verify how far its curriculum structuring and its pedagogical implementation have allowed the student to develop an integral education, which joins simultaneously both humanist and critical formation, plus to the technical-professional